Factors that determine financial performance of SMEs in Malaysia - Abdul Razak, Dzuljastri; Othman, Anwar Hasan Abdullah; Zulkifly, Umi Waheeda I'zaaz; Zakaria, Fatin Shafiqah (ABRN Asia, 2021)
Small and Medium Enterprises (SMEs) has been recognized as the backbone to a country’s economic development and social benefits. Malaysian SMEs contributed 38.8% to overall GDP, 17.3% to total exports and 66.2% to total employment. Huge budget allocations were put every year to enhance and encourage the improvement on SMEs. However, it was found that many of the SMEs failed within the first years of its business operations despite various programs and initiatives by the government agencies. Therefore, this paper aims to determine factors that determine sustainable financial performance of SMEs in Malaysia namely, Financial Knowledge, Financial Attitude, Financial Socialization Agents, Financial Skills and Accounting Skills. The relationship of these factors towards SMEs performance is measured using regression and factor analysis conducted using the Statistical Package for the Social Sciences (SPSS) software. Findings reveal that all factors have a significant relationship with SME financial performance in Malaysia except for financial skills. Hence, the authority especially those that provide programmes involving SME can emphasize on the significant factors in their effort to improve the financial performance and increase the survival of SMEs in the industry.